The branch will not break : poems - Wright, James, 1927-1980. (Middletown, Conn. : Wesleyan University Press, 1963)
A new book of poetry from a Pulitzer Prize-winning master poet.
As I step over a puddle at the end of winter, I think of an ancient Chinese governor -- Goodbye to the poetry of calcium -- In fear of harvests -- Three stanzas from Goethe -- Autumn begins in Martins Ferry, Ohio -- Lying in a hammock at William Duffy's farm in Pine Island, Minnesota -- The jewel -- In the face of hatred -- Fear is what quickens me -- A message hidden in an empty wine bottle that I threw into a gully of maple trees one night at an indecent hour -- Stages on a journey westward -- How my fever left -- Miners -- In Ohio -- Two poems about President Harding -- Eisenhower's visit to Franco, 1959 -- In memory of a Spanish poet -- The undermining of the defense economy -- Twilights -- Two hangovers -- Depressed by a book of bad poetry, I walk toward an unused pasture and invite the insects to join me -- Two horses playing in the orchard -- By a lake in Minnesota -- Beginning -- From a bus window in Central Ohio, just before a thunder shower -- March -- Trying to pray -- Two spring charms -- Spring images -- Arriving in the country again -- In the cold house -- Snowstorm in the Midwest -- Having lost my sons, I confront the wreckage of the moon : Christmas 1960 -- American wedding -- A prayer to escape from the market place -- Rain -- Today I was happy, so I made this poem -- Mary Bly -- To the evening star : Central Minnesota -- I was afraid of dying -- A blessing -- Milkweed -- A dream of burial.
Electronic reproduction.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: American poetry; American poetry -- 20th century; Poésie américaine.; Poésie américaine -- 20e siècle.; POETRY -- American -- General; American poetry; 1900 - 1999; American poetry